Flexible nasopharyngolaryngoscopy: Evaluation and appraisal of its effectiveness and diagnostic yield, The Nigerian experience - Shuaib Kayode Aremu (Journal of Family Medicine and Primary Care, 2019)
Background: Fiber-optic nasopahryngolaryngoscopy is a visual examination of the larynx and its related structures. It is an effective procedure for ascertaining the causes of laryngeal disorders, pain in the throat, and difficulty in swallowing and hence should be used in all ENT clinics routinely. This study established the diagnostic effectiveness of fiber-optic nasoparyngolaryngoscopy in our clinics in Federal Teaching Hospital Ido-Ekiti, Ekiti State, Nigeria. It also analyzed the indications, findings, and the role it played in the management of the patients. Materials and Methods: This was a one-year (May 2015 to April 2019) prospective study involving 100 patients who had nasolaryngoscopy procedures done in the ear, nose, and throat (ENT) surgery clinics of Federal Teaching Hospital Ido-Ekiti, Ekiti State, Nigeria. A structured proforma was designed for the study. The data collected included the biodata (age and sex), presenting symptoms/indications for the procedure and findings at nasopharyngolaryngoscopy. These were entered into SPSS version 24 computer software and analyzed descriptively. Results: A total of 100 patients had the procedure during the study period. The mean age and standard deviation of respondents were 47.3 ± 16.4 years with more than half (71.0%) being females. The male to female ratio was 1:2.4. Majority of the patients were in the age range of 60 years and above (28.0%) while the minority were less than 20 years (6.0%). Conclusion: This study substantiates the contention that flexible nasopharyngolaryngoscopy is a very effective diagnostic tool for the patients presenting with upper airway related symptoms.